Fabrication of micro holes in CFRP laminates using EDM. (January 2018) - Kumar, Ravinder; Agrawal, Pramod Kumar; Singh, Inderdeep
Abstract: Carbon fiber reinforced plastics (CFRPs) are being used in various applications due to their light weight and good mechanical properties. However, the machinability of CFRPs is not good owing to machining induced damage. Moreover, the machining of micro features in CFRP products is a challenging task. The present research endeavour is an attempt to experimentally investigate a novel micro-size through hole electric discharge drilling (EDD) process for CFRPs. Through holes of diameter 110 μm were drilled using tungsten carbide electrodes (fabricated with wire electric discharge grinding). Experiments have been conducted by selecting input variables as voltage, capacitance and tool speed. A comparison of aspect ratio has been performed among the previous experimental studies and the current investigation. An aspect ratio of 10.9 (highest till date) has been achieved during drilling a micro hole of 110 μm diameter and 1.2 mm depth. Analysis of variance has been performed using Taguchi design of experiments and optimized set of parameters has been reported for maximum material removal rate and minimum tool were rate. The article also discuss the problems faced and their solutions, during drilling of micro through holes in carbon fiber reinforced polymer matrix composites.